2014
DOI: 10.1002/j.2334-5837.2014.tb03132.x
|View full text |Cite
|
Sign up to set email alerts
|

1.2.3 Towards a semantic‐based representation and computation of quantitative indexes for quality management of requirements

Abstract: Quality management of requirements has seen a dramatic increase of the amount of applications, management platforms, data, etc. gaining momentum in the Systems Engineering area and more specifically in the deployment of the next wave of critical system. In this context, one of the next big things lies in the creation of quality functions that can automatically detect and make decisions according to natural‐language based requirements specifications and models. In this sense quality indicator of requirements se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…25 th Annual INCOSE International Symposium (IS2015) Seattle, July 13-16, 2015 As an example of use, let's suppose that a vocabulary has been created to compile all terms used in the development of a product (a "car"), see Listing 1. Although some initial attempts can be found (Alvarez-Rodríguez, Fuentes, et al 2014) to represent such knowledge, OSLC does not define yet any particular vocabulary. That is why the RHSP model is used to represent these concepts and their relationships.…”
Section: Case Study: Implementation Of the Oslc Km Specification And mentioning
confidence: 99%
See 2 more Smart Citations
“…25 th Annual INCOSE International Symposium (IS2015) Seattle, July 13-16, 2015 As an example of use, let's suppose that a vocabulary has been created to compile all terms used in the development of a product (a "car"), see Listing 1. Although some initial attempts can be found (Alvarez-Rodríguez, Fuentes, et al 2014) to represent such knowledge, OSLC does not define yet any particular vocabulary. That is why the RHSP model is used to represent these concepts and their relationships.…”
Section: Case Study: Implementation Of the Oslc Km Specification And mentioning
confidence: 99%
“…Let's also suppose that a requirements management tool is used to create requirements generating an OSLC-based requirement, see Listing 2. Since some tools (Génova et al 2011) can be found to check the quality of requirements and export them as OSLC (Alvarez-Rodríguez, Fuentes, et al 2014), these metrics can be used to enrich the description of the requirements, see Listing 3. Finally, the under development "car" must be depicted as a Product Breakdown Structure (PBS), see Figure 5.…”
Section: Case Study: Implementation Of the Oslc Km Specification And mentioning
confidence: 99%
See 1 more Smart Citation
“…The OSLC, as an integration bus, is expected to be the next big thing in systems development elevating the meaning of information resources through semantic-based technologies. That is why, authors present a model to represent, validate and compute a product breakdown structure using RDF-based vocabularies, see Figure 1 and Figure 2, extending the previous work in (J. M. Alvarez-Rodríguez, Fuentes, et al 2014). …”
Section: Introductionmentioning
confidence: 96%
“…Classes and properties to model the elements in the PBS as an OSLC Resource. Since the structure and the computation processes can be built on the top of an existing RDF vocabulary it is then possible to make a translation to a generic SPARQL query (includes the basic OWA operator), see Listing 1 and the extended explanation of the computation in (J. M. Alvarez-Rodríguez, Fuentes, et al 2014 This definition of a PBS contains two major implications:…”
mentioning
confidence: 99%